Pembangunan Sistem Monitoring Rumah Menggunakan Mikrokomputer - Reno Putra Prawira; Adam Hendra Brata; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The house left by homeowener became one of the target robbers to commit a crime. Therefore security is a mandatory requirement of every homeowner. One example of traditional systems that are still widely used are home alarms. But home alarms are offline, in the sense that if the homeowner is out of the house, then the danger alarm can not be accepted by the home owner. Because of these problems the research was conducted to make home monitoring systems using microcomputers. Microcomputers used in this research are Raspberry Pi 3 Model B. There are four main processes in this research including engineering needs, design, implementation, and system testing. The result of engineering requirement got eight functional requirement and two non functional requirement for software on microcomputer. While in the smartphone software obtained 20 functional requirements. Needs that have been obtained as a design system with the results of architecture design in the form of data design, architecture design, interface design, component design, and hardware design. The design of the created system is implemented into the program code using Javascript followed by hardware implementation. Home monitoring systems have been successfully tested using white box testing techniques on unit testing and black box testing techniques on validation testing. The result of performance test obtained time of giving danger notification that is a pretty good between 5-9 seconds.